First, plug in the numbers where the variables are, so you get this:

3(11) + 5 (4)

Then, mulitply the 3 and 11. so you have this:

33+5 (4)

Next, multiply the 5 and 4. So you have this:

33+20

Finally, add the numbers to get 53. That is the answer.

- replace the 3 times X with 3 times 11

- replace the 5 times Y with 5 times 4

- then once you have those two answers you add them up

- finally you have your answer

3 x (X) + 5 x( Y) =

3 x 11 + 5 x 4 =

33 + 20 =53

ans: 33

This can be done by calculating the given values in the given equation. This is done as follows,

Given equation, 3x+5y

On Substituting the given values x=11,y=4 in the given equation

3(11)+5(4)=>33+20=>53.

Hence, the obtained result is 53.

Plug in the values of x and y in the equation given:

= 3x + 5y

= 3(11) + 5(4)

= 33 + 20

= 53

Therefore the value of 3x + 5y is 53 when x = 11 and y = 4.

Thank you for the question.

You simply substitute the given value x=11 and y=4

so the equation will be 3(11)+5(4)=n

then simplify, 3(11) is 33 and 5(4) is 20,

33+20 is equal to 53

that's it!

Its really quite simple with the given equation 3x+5y, plug in the given integer values of x and y and there isyour answer

3(11)+5(4)=53

Its really quite simple with the given equation 3x+5y, plug in the given integer values of x and y and there isyour answer

3(11)+5(4)=53

Is this some sort of joke? My dog figured this one out:

kjhfdskjhdfuyvcm,bvuhiubsdmcyui fofncnf=53

Thanks pup!